High fructose consumption may have part in the pathophysiology of coronary artery ectasia - Kuyumcu, Aliye; Serdar Kuyumcu, Mevlut (Annals of Medical Research, 2021)
Aim: A coronary artery may partly become a half or one diameter larger than an adjoining normal one as observed on angiograms, which is called coronary artery ectasia (CAE). There is strong evidence that oxidative stress and inflammation may contribute to the CAE pathophysiology, potentially due to higher fructose intake. Our study aims to determine the effects of the amount of fructose consumed on isolated CAE. Material and Methods: The study group consists of the patients with stable angina pectoris who had coronary angiography (CAG) reports dated from December 2018 to April 2019. Based on these reports, sampling was made as follow: the patient or CAE group of 50 patients also with isolated CAE and the control group of 50 patients with normal coronary flow pattern (NCF). A comparative analysis was performed using the exact data of both groups including nutrient consumption.Results: The patient group with higher high-sensitivity C-reactive protein levels (p = 0.029), greater platelet count (p = 0.015), and increased hypertension rate (p = 0.012) were observed to have higher energy in total (p = 0.008), carbohydrate (p = 0.003), and fructose intake (p0.001). Multivariable logistic regression analyses demonstrated that rising Hs-CRP levels (p = 0.031), greater platelet count (p = 0.017), higher fructose intake (p = 0.029), and increased hypertension (p = 0.032) were individually associated with CAE.Conclusion: In the CAE group higher fructose consumption was observed and thus determined to potentially contribute to the CAE pathophysiology.
Keywords: Atherosclerosis; Coronary artery ectasia; fructose consumption